1984
DOI: 10.1148/radiology.150.2.6691093
|View full text |Cite
|
Sign up to set email alerts
|

Hirschsprung disease: accuracy of the barium enema examination.

Abstract: To determine the relative accuracy of the various radiologic signs of Hirschsprung disease (HD), we retrospectively reviewed both radiographs obtained after a barium enema and the medical records of 62 children who had surgery to prove or exclude the diagnosis of HD. The visualization of a rectosigmoid transition zone was highly predictive of HD, but nonvisualization did not rule out HD. A false positive transition zone at the splenic flexure was seen in four neonates who had small left colon syndrome rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
3

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 0 publications
3
36
1
3
Order By: Relevance
“…A delay in passage of meconium is the most pertinent observation in the neonate suspected of having HD (80%). 31 In the present study we had observed abdominal distension, lack of meconium defecation, and constipation were the most common clinical symptoms with frequencies of 15 (78.9%), 11 (57.8%), and 14 (73.68%) respectively. Whereas normal babies pass meconium within 24 hours, and even up to 48 hours, any baby who passes no or little meconium even after 24 hours should be investigated for HD.…”
Section: Discussionsupporting
confidence: 51%
“…A delay in passage of meconium is the most pertinent observation in the neonate suspected of having HD (80%). 31 In the present study we had observed abdominal distension, lack of meconium defecation, and constipation were the most common clinical symptoms with frequencies of 15 (78.9%), 11 (57.8%), and 14 (73.68%) respectively. Whereas normal babies pass meconium within 24 hours, and even up to 48 hours, any baby who passes no or little meconium even after 24 hours should be investigated for HD.…”
Section: Discussionsupporting
confidence: 51%
“…Idade ( O enema baritado para diagnóstico do megacolo congê-nito aganglionar tem sido considerado um instrumento pouco preciso no recém-nascido, quando a aganglionose é total e nas formas de acometimento ultracurto [7][8][9] . Num grupo de 58 crianças constipadas, a presença da zona de transição no retosigmóide, rotineiramente associada à aganglionose, foi identificada em 9 crianças com constipação funcional.…”
Section: Constipação Funcional Má Formação Dos Plexos (N=47) Mioentérunclassified
“…Da mesma forma que o enema baritado, a manometria anorretal não apresenta 100% de acurácia para o diagnós-tico diferencial [5][6][7][8][9] , identificando-se resultados falsos negativo 10-11 e falsos positivos [12][13][14] . Na última década, os dados da literatura têm registrado uma confiabilidade variável da manometria na identificação da doença de Hirschsprung e das displasias neuronais [15][16][17][18] .…”
Section: Introductionunclassified
“…Olguların %65'inde geçiş zonu rektosigmoid bölgededir (Resim 4). Agangliyonik segmentin proksimalinde kolon EĞİTİCİ NOKTA EĞİTİCİ NOKTA segmentleri ve ince bağırsaklar dilatedir [16]. Total aganglionozis ve çok kısa segment hastalıkta tanı güç olup baryumlu inceleme normal olabilir [17].…”
Section: Kolon Tetkikinin Tanı Amaçlı Kullanıldığı Bazı Hastalıklarunclassified